A complete small‐signal model of GaAs dual‐gate HEMT. (7th April 2022) - Huang, Yuhan; Liu, Jun; Chen, Zhanfei
Abstract: A complete small‐signal model of dual‐gate HEMT is proposed, considering the parasitic element effects. To extract the intrinsic elements accurately, the parasitic elements are eliminated by using a new method in this paper. It is realized by constructing two simple three‐port matrices and eliminating them with the features of π ‐type and T‐type networks. This method is fast and accurate. Dual‐gate HEMTs could be regarded as a cascode connection of two single‐gate HMETs. A dual‐gate HEMT is fabricated on a commercial 0.25 μm GaAs technology to verify the proposed the extraction method. The result shows a good agreement between measured and simulated data over a wide frequency range.